Blockchain Technology Adoption - Cesario, Francisco (2023)
Cesario, F., Costa, C. J., Aparicio, M., & Aparicio, J. T. (2023). Blockchain Technology Adoption: Factors Influencing Intention and Usage. In A. R. da Silva, M. M. da Silva, J. Estima, C. Barry, M. Lang, H. Linger, & C. Schneider (Eds.), Information Systems Development, Organizational Aspects and Societal Trends (ISD2023 Proceedings) Instituto Superior Técnico. https://aisel.aisnet.org/isd2014/proceedings2023/managingdevops/1/ --- Funding: The authors acknowledge financial support via ADVANCE- CSG from the Fundação para a Ciência and Tecnologia (FCT Portugal) through research grant numbers UIDB/04521/2020; research grant UIDB/04152/2020—Centro de Investigação em Gestão de Informação (MagIC); and research grant UI/BD/153587/2022.